The Genus Guerrerostrongylus (Nematoda: Heligmonellidae) in Cricetid Rodents from the Atlantic Rain Forest of Misiones, Argentina: Emended Description of Guerrerostrongylus zetta (Travassos, 1937) and Description of a New Species - Digiani, María Celina (2012)
Fil: Digiani, María Celina. División Zoología Invertebrados. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina